Pengaruh Terapi Aktivitas Kelompok (Tak) Orientasi Realita Terhadap Tingkat Fungsi Kognitif Pada Lansia Demensia Di Griya Lansia Jannati - Ambo, Apriliya (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: Physical decline can have an impact on changes in the cognitive function of the elderly who become forgetful, so treatment needs to be carried out to improve the cognitive function of the elderly, such as group reality orientation therapy. The research aims to determine the effect of reality-oriented group activity therapy (TAK) on the level of cognitive function in elderly people with dementia at Griya Lansia Jannati. Methods: The research method used is pre-experimental research with one group pre-post test design where the researcher reveals a cause-and-effect relationship by involving a group of subjects who are observed before and after being given treatment. Results: The results of this study show that the level of cognitive function before reality-oriented group activity therapy (TAK) in elderly people with dementia at Griya Lansia Jannati, the majority were mild, 6 respondents (60%). Then the level of cognitive function after reality orientation group activity therapy (TAK) in elderly people with dementia at Home Elderly Jannati, the majority were normal, 7 respondents (70%). So after carrying out the paired t-test, it was found that there was an influence of reality-oriented group activity therapy (TAK) on the level of cognitive function in elderly people with dementia at Home for the Elderly Jannati with a p-value of 0.005 (<α 0.05). Conclusion: From this research data, it can be seen that there was a change in the cognitive function of the elderly after being given reality orientation TAK, where previously the majority of respondents had mild cognitive dysfunction, to a normal level of cognitive function so it can be seen that this therapy can improve the cognitive function of the elderly